Respuesta :
Judging by the question I noticed that I can simplify the equation 3x-x+2=12 by one step.
The outcome of simplification should be 2x+2=12.
Next you must subtract 2 from both sides to isolate the x. The new equation should be 2x = 10.
Lastly you must divide both sides by 2, the answer you should get is x=5, D.
The outcome of simplification should be 2x+2=12.
Next you must subtract 2 from both sides to isolate the x. The new equation should be 2x = 10.
Lastly you must divide both sides by 2, the answer you should get is x=5, D.
Combine like terms:
[tex]3x - x = 2x[/tex]
[tex]2x + 2 = 12[/tex]
Subtract 2 from both sides:
[tex]2x = 10[/tex]
Divide both sides by 2 to get x by itself:
[tex]x = 5[/tex]
The value of x is 5.
[tex]3x - x = 2x[/tex]
[tex]2x + 2 = 12[/tex]
Subtract 2 from both sides:
[tex]2x = 10[/tex]
Divide both sides by 2 to get x by itself:
[tex]x = 5[/tex]
The value of x is 5.